A method for manufacturing a magnesium alloy wind power blade

By using magnesium alloys and superplastic forming technology to manufacture wind turbine blades, the problems of long manufacturing cycles, non-recyclability, and high molding difficulty of traditional composite materials have been solved, achieving lightweighting, efficiency improvement, and environmental enhancement, making them suitable for large-scale wind power equipment.

CN123039737APending Publication Date: 2026-11-06XIAN SIFANG ULTRA LIGHT MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611329440.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing wind turbine blade manufacturing technologies suffer from problems such as long manufacturing cycles, difficulty in controlling dimensional deviations, non-recyclability, high material costs, susceptibility to internal defects, and difficulty in superplastic molding, especially in terms of scaling up and lightweighting.

Method used

Magnesium alloys are used to replace traditional composite materials. The skin is manufactured using superplastic forming technology and other components are manufactured using isothermal forging technology. Combined with grain refinement pretreatment and segmented forming process, magnesium alloy wind turbine blades can be manufactured.

Benefits of technology

It achieves lightweight blades (weight reduction of more than 40%), improves manufacturing efficiency by dozens of times, is 100% recyclable, and has fatigue performance superior to traditional composite materials, meeting the needs of the large-scale and green development of wind power equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123039737A_ABST
    Figure CN123039737A_ABST
Patent Text Reader

Abstract

A method for manufacturing magnesium alloy wind turbine blades, belonging to the field of wind power equipment manufacturing technology, includes the following steps: Step 1: Pre-treatment of magnesium alloy sheet for grain refinement; Step 2: Fabrication of the windward and leeward skins of the magnesium alloy wind turbine blades using superplastic forming technology; superplastic forming is carried out in a dedicated hot forming press; Step 3: Manufacturing the main beam cap and web using isothermal forging technology; Step 4: Surface treatment of the formed magnesium alloy wind turbine blades; Step 5: Assembly of the magnesium alloy wind turbine blades. This invention uses magnesium alloy to replace traditional glass fiber / carbon fiber-epoxy resin composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wind power equipment manufacturing technology, specifically a method for manufacturing magnesium alloy wind turbine blades. Background Technology

[0002] Wind turbine blades are the core components of wind turbines, converting wind energy into mechanical energy, and directly determine the power generation efficiency and operational reliability of the unit. Currently, large wind turbine blades mainly adopt vacuum injection molding. Although this process is the industry mainstream, it has significant inherent drawbacks: long manufacturing cycle, difficulty in precisely controlling dimensional deviations, non-recyclable epoxy resin matrix, and the tendency to generate internal defects such as bubbles and dry spots during injection, affecting the long-term service safety of the blades. While prepreg laying technology can improve fiber content and molding quality, it suffers from high material costs, demanding storage conditions, and low laying efficiency. As wind power equipment accelerates towards larger size, lighter weight, and greener designs, the bottlenecks of traditional composite material blades in terms of recyclability, manufacturing efficiency, and lightweight potential are becoming increasingly apparent, necessitating the search for alternative materials and innovative manufacturing processes.

[0003] Magnesium alloys are currently the lightest metallic structural materials used in engineering applications, with a density approximately two-thirds that of aluminum alloys and one-quarter that of steel. They also possess high specific strength and stiffness, excellent vibration damping performance, and are 100% recyclable, making them ideal candidates for lightweight wind turbine blade manufacturing. Superplastic forming technology utilizes the high plasticity of metallic materials in a fine-grained state for precision forming. Its main mechanism is grain boundary slip, accompanied by dynamic recrystallization and diffusion creep. This technology has already been applied in the automotive industry; for example, General Motors uses rapid plastic forming processes to manufacture body panels, and the Porsche 911 GT3 RS roof uses magnesium alloys prepared using superplastic forming technology to achieve weight reduction. However, introducing superplastic forming into wind turbine blade manufacturing faces several technical challenges, including blade dimensions far exceeding equipment capabilities, the difficulty of integrating airfoil surfaces with the load-bearing structure, uneven thinning due to air expansion easily leading to localized cracking, and extremely high reliability requirements for segmented connections. This invention proposes a method for manufacturing magnesium alloy wind turbine blades. The method uses superplastic forming technology to manufacture the skin and isothermal forging technology to manufacture other components. It mainly solves the problems of non-recyclability of composite material wind turbine blades, long manufacturing cycle, insufficient strength of superplastic formed parts as the main load-bearing structure, uneven thickness and local cracking during the superplastic forming process. Summary of the Invention

[0004] This invention provides a method for manufacturing magnesium alloy wind turbine blades to overcome the deficiencies in the prior art.

[0005] This invention is achieved through the following technical solution: A method for manufacturing a magnesium alloy wind turbine blade includes the following steps: Step 1: Perform grain refinement pretreatment on magnesium alloy sheet to obtain superplastic billet with an average grain size ≤10μm; Step 2: The windward and leeward skins of the magnesium alloy wind turbine blades are manufactured using a superplastic forming process; the superplastic forming is carried out in a dedicated thermoforming press. Step 3: Manufacture the main beam cap and web using isothermal forging technology; Step 4: The formed magnesium alloy wind turbine blades need to undergo surface treatment; Step 5: Assemble the magnesium alloy wind turbine blades.

[0006] The method for manufacturing a magnesium alloy wind turbine blade as described above, wherein the magnesium alloy sheet comprises the following substances in mass percentage: Al 2.5-3.5%, Zn 0.7-1.3%, Mn 0.2-1.0%, Si ≤0.10%, Cu ≤0.05%, Ni ≤0.005%, Fe ≤0.005%, with the remainder being Mg.

[0007] The method for manufacturing a magnesium alloy wind turbine blade as described above includes a grain refinement pretreatment: heating the magnesium alloy sheet to 350–420°C and holding it at that temperature for 2–4 hours, followed by 2–4 passes of warm rolling, with a reduction of 15%–25% per pass and a rolling temperature of 250–350°C. This can further refine the grain size to 3–8 μm. By refining the material grains through the above two methods, not only is the superplasticity improved, but it also helps to improve the room temperature strength and fatigue performance of the blade after forming.

[0008] The manufacturing method of a magnesium alloy wind turbine blade as described above, wherein the preparation process of the windward and leeward skins of the magnesium alloy wind turbine blade is as follows: Step 1: Cutting magnesium alloy sheet blanks; Step 2: Segmented molding of the skin: Place the cut magnesium alloy sheet blanks into the mold; Step 2-1: Low-pressure rapid bonding; Step 2-2: Uniform extension under medium pressure; Steps 2-3: High-pressure precision molding; Step 3: Open the mold and remove the parts.

[0009] In the manufacturing method of a magnesium alloy wind turbine blade as described above, the thickness of the magnesium alloy sheet blank used for the root region is 3.0-5.0 mm; the thickness of the magnesium alloy sheet blank used for the middle region is 2.0-3.0 mm; and the thickness of the magnesium alloy sheet blank used for the blade tip region is 1.5-2.0 mm. A gradual transition is adopted between each region, and the length of the transition zone is not less than 200 mm, so as to avoid stress concentration and deformation inconsistency caused by abrupt changes in thickness.

[0010] As described above, in the manufacturing method of a magnesium alloy wind turbine blade, the low-pressure rapid bonding operation air pressure for the segmented manufacturing of the skin is 0.15-0.25 MPa, the operation time is 30-120 s, and the operation temperature is 400-500℃. This allows the magnesium alloy sheet to be quickly bonded to the approximate outline of the mold cavity. During this stage, the air pressure is relatively low, and the material deformation rate is moderate, avoiding excessive thinning in some areas due to excessively rapid initial deformation. This stage corresponds to the initial formation of the large curvature area of ​​the blade skin. The operating pressure for the segmented manufacturing of the aforementioned skin, characterized by medium-pressure uniform stretching, is 0.4–0.7 MPa, the operating time is 8–10 min, and the operating temperature is 400–500 °C, at a rate of 1 × 10⁻⁶. -3 ~5×10 -3 s -1 The strain rate allows the material to fully extend and fill the mold cavity, corresponding to the uniform thinning and area expansion of the blade skin body area; The high-pressure precision molding process for segmented skin manufacturing operates at a pressure of 0.8–1.2 MPa, a time of 5–15 minutes, and a temperature of 400–500°C. This ensures the material perfectly conforms to the detailed features of the mold cavity (such as the leading edge, trailing edge, and local reinforcing ribs), while simultaneously achieving stress relaxation and structural stabilization. This stage corresponds to the precision forming of small radius-of-curvature regions such as the leading and trailing edges of the blade.

[0011] In the above-described method for manufacturing a magnesium alloy wind turbine blade, after the skin segmentation molding is completed, the mold temperature is reduced to below 200°C at a rate of 5-15°C / min while maintaining air pressure. Then, the pressure is released, the mold is opened, and the molded part is removed. The slow cooling process helps to avoid thermal stress and warping deformation and maintain molding accuracy.

[0012] The manufacturing method of a magnesium alloy wind turbine blade described above, wherein the isothermal die forging process for manufacturing the main beam cap and web plate is as follows: the grooved cross-section of the main beam cap 1 and web plate 2 is prepared by isothermal die forging, the die forging temperature is 400-460℃, the unit pressure is 10-80MPa, the die forging speed is 0.5-10mm / s, the holding time is 30-300s, the billet preheating temperature is 350-450℃, the preheating time is 10-30min, the flange width is 50-150mm, the web plate height is 30-100mm, the wall thickness is 2.5-5.0mm, and the mold and the billet are kept at the same (or similar) temperature throughout the forming process. By utilizing the low flow stress and high plasticity of the material at high temperature, precision forming is achieved under relatively low unit pressure.

[0013] The manufacturing method of a magnesium alloy wind turbine blade as described above includes the following surface treatment operations after the magnesium alloy wind turbine blade is formed: removing surface oxide scale and impurities using a stainless steel wire brush or sandblasting; then performing a chemical conversion film treatment: using phosphate or chromate treatment to form a protective conversion film on the surface, the thickness of the protective conversion film being 1-5 μm; finally, spraying an organic coating, the organic coating including an epoxy zinc-rich primer, an epoxy intermediate coat, and a polyurethane or fluorocarbon topcoat, the thickness of the epoxy zinc-rich primer being 30-50 μm, the thickness of the epoxy intermediate coat being 40-60 μm, and the thickness of the polyurethane or fluorocarbon topcoat being 40-60 μm.

[0014] The method for manufacturing a magnesium alloy wind turbine blade as described above involves assembling the blade using segmented bolt connections. Flange structures are installed at the joints of the segments, with a flange width of 50–150 mm and a flange thickness of 2–3 times the thickness of the skin. High-strength bolts are evenly arranged along the circumference of the flange, and the number of bolts is determined based on load calculations. The bolt connections are reversible, facilitating segmented transportation and on-site assembly, as well as maintenance and segmented replacement.

[0015] The advantages of this invention are: This invention uses magnesium alloy to replace the traditional glass fiber / carbon fiber-epoxy resin composite material. Attached Figure Description

[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0017] Figure 1 This is a flowchart of the present invention; Figure 2 This is a schematic diagram of the skin of the magnesium alloy wind turbine blade of the present invention; Figure 3 This is a schematic diagram of the main beam cap and web of the present invention.

[0018] Reference numerals: 1. Main beam cap; 2. Web plate. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] like Figure 1 As shown, a method for manufacturing a magnesium alloy wind turbine blade includes the following steps: Step 1: Perform grain refinement pretreatment on magnesium alloy sheet to obtain superplastic billet with an average grain size ≤10μm; Step 2: The windward and leeward skins of the magnesium alloy wind turbine blades are manufactured using a superplastic forming process; the superplastic forming is carried out in a dedicated thermoforming press. Step 3: Manufacture the main beam cap and web using isothermal forging technology; Step 4: The formed magnesium alloy wind turbine blades need to undergo surface treatment.

[0021] Preferably, the magnesium alloy sheet described in this embodiment comprises the following substances in mass percentage: Al 2.5-3.5%, Zn 0.7-1.3%, Mn 0.2-1.0%, Si ≤0.10%, Cu ≤0.05%, Ni ≤0.005%, Fe ≤0.005%, and the remainder is Mg.

[0022] Preferably, the grain refinement pretreatment described in this embodiment is as follows: heating the magnesium alloy sheet to 350-420°C and holding it at that temperature for 2-4 hours, followed by 2-4 passes of warm rolling, with a reduction of 15%-25% per pass and a rolling temperature of 250-350°C, which can further refine the grain size to 3-8 μm. By refining the material grains through the above two methods, not only is the superplasticity improved, but it also helps to improve the room temperature strength and fatigue performance of the formed blade.

[0023] like Figure 2 As shown, preferably, the manufacturing process of the windward and leeward skins of the magnesium alloy wind turbine blade described in this embodiment is as follows: Step 1: Cutting magnesium alloy sheet blanks; Step 2: Segmented molding of the skin: Place the cut magnesium alloy sheet blanks into the mold; Step 2-1: Low-pressure rapid bonding; Step 2-2: Uniform extension under medium pressure; Steps 2-3: High-pressure precision molding; Step 3: Open the mold and remove the parts.

[0024] Preferably, in this embodiment, the cutting thickness of the magnesium alloy sheet blank used for the root region (connection section with the hub) is 3.0-5.0 mm; the cutting thickness of the magnesium alloy sheet blank used for the middle region is 2.0-3.0 mm; and the cutting thickness of the magnesium alloy sheet blank used for the blade tip region is 1.5-2.0 mm. A gradual transition is adopted between each region, and the length of the transition zone is not less than 200 mm, so as to avoid stress concentration and deformation inconsistency caused by abrupt changes in thickness.

[0025] Preferably, the operating air pressure for the low-pressure rapid bonding of the segmented skin manufacturing described in this embodiment is 0.15-0.25 MPa, the operating time is 30-120 s, and the operating temperature is 400-500℃, so that the magnesium alloy sheet can be quickly bonded to the approximate outline of the mold cavity. At this stage, the air pressure is low and the material deformation rate is moderate, avoiding excessive thinning in some areas due to excessively rapid initial deformation. This stage corresponds to the initial forming of the large curvature area of ​​the blade skin. The operating pressure for the segmented manufacturing of the aforementioned skin, characterized by medium-pressure uniform stretching, is 0.4–0.7 MPa, the operating time is 8–10 min, and the operating temperature is 400–500 °C, at a rate of 1 × 10⁻⁶. -3 ~5×10 -3 s -1 The strain rate allows the material to fully extend and fill the mold cavity, corresponding to the uniform thinning and area expansion of the blade skin body area; The high-pressure precision molding process for segmented skin manufacturing operates at a pressure of 0.8–1.2 MPa, a time of 5–15 minutes, and a temperature of 400–500°C. This ensures the material perfectly conforms to the detailed features of the mold cavity (such as the leading edge, trailing edge, and local reinforcing ribs), while simultaneously achieving stress relaxation and structural stabilization. This stage corresponds to the precision forming of small radius-of-curvature regions such as the leading and trailing edges of the blade.

[0026] Preferably, after the skin segment molding process described in this embodiment is completed, the mold temperature is reduced to below 200°C at a rate of 5-15°C / min while maintaining air pressure. Then, the pressure is released, the mold is opened, and the molded part is taken out. The slow cooling process helps to avoid thermal stress and warping deformation and maintain molding accuracy.

[0027] like Figure 3As shown, preferably, the operation of manufacturing the main beam cap and web plate using the isothermal die forging technology described in this embodiment is as follows: the grooved cross-section of the main beam cap 1 and web plate 2 is prepared by isothermal die forging, the die forging temperature is 400-460℃, the unit pressure is 10-80MPa, the die forging speed is 0.5-10mm / s, the holding time is 30-300s, the billet preheating temperature is 350-450℃, the preheating time is 10-30min, the flange width is 50-150mm, the web plate height is 30-100mm, the wall thickness is 2.5-5.0mm, and the mold and billet maintain the same (or similar) temperature throughout the forming process. By utilizing the low flow stress and high plasticity of the material at high temperatures, precision forming is achieved under relatively low unit pressure.

[0028] Preferably, the surface treatment operation of the magnesium alloy wind turbine blade after forming in this embodiment is as follows: removing the surface oxide scale and impurities by using a stainless steel wire brush or sandblasting; then performing chemical conversion film treatment: using phosphate or chromate treatment to form a protective conversion film on the surface, the thickness of the protective conversion film being 1-5 μm; finally, spraying an organic coating, the organic coating including epoxy zinc-rich primer, epoxy intermediate paint and polyurethane or fluorocarbon topcoat, the thickness of the epoxy zinc-rich primer being 30-50 μm, the thickness of the epoxy intermediate paint being 40-60 μm, and the thickness of the polyurethane or fluorocarbon topcoat being 40-60 μm.

[0029] Preferably, the magnesium alloy wind turbine blades described in this embodiment are assembled using segmented bolt connections. Flange structures are provided at the joints of the segments. The flange width is 50-150mm, and the flange thickness is 2-3 times the thickness of the skin. High-strength bolts are evenly arranged along the circumference of the flange. The number of bolts is determined based on load calculations. The bolt connection is reversible, which facilitates segmented transportation and on-site assembly, and makes maintenance and segmented replacement convenient.

[0030] Example 1 (8m-class small magnesium alloy wind turbine blade) This embodiment takes the manufacturing of an 8m-class small magnesium alloy wind turbine blade as an example, and is applicable to the segmented blade unit of small and medium-sized wind turbine generator sets or large units. The specific steps are as follows.

[0031] Step 1: Grain Refinement Pretreatment AZ31B magnesium alloy sheet was selected, with the following chemical composition by mass percentage: Al 3.0%, Zn 1.0%, Mn 0.5%, Si 0.05%, Cu 0.02%, Ni 0.003%, Fe 0.003%, and the balance being Mg. The sheet was heated to 380℃ and held for 3 hours, followed by three passes of warm rolling with reductions of 20%, 18%, and 15% respectively at a rolling temperature of 300℃. After this treatment, the grain size was measured under a metallographic microscope using the cross-section method, yielding a superplastic billet with an average grain size of approximately 6 μm.

[0032] Step 2: Superplastic molding to create the skin Magnesium alloy sheet blanks are cut with a thickness of 3.0 mm at the root area, 2.0 mm at the middle area, and 1.5 mm at the tip area, with a 200 mm long gradient transition zone between each area.

[0033] The cut blank is placed into the thermoforming press mold, the mold temperature is 430℃. A three-step pneumatic loading process is adopted: Low-pressure rapid bonding stage: operating air pressure 0.18MPa, operating time 45s, operating temperature 430℃, so that the sheet material can be quickly bonded to the approximate outline of the mold cavity. Medium-pressure uniform extension stage: operating pressure 0.50 MPa, operating time 8 min, operating temperature 430℃, strain rate 3×10⁻⁶ -3 s -1 This allows the material to fully expand and fill the mold cavity; High-pressure precision molding stage: operating air pressure 0.9MPa, operating time 8min, operating temperature 430℃, so that the material can completely fit the detailed features of the mold cavity (such as the leading edge, trailing edge, etc.), while realizing stress relaxation and tissue stabilization.

[0034] After molding, the mold temperature is reduced to below 200℃ at a rate of 10℃ / min while maintaining air pressure. Then, the pressure is released, the mold is opened, and the molded part is removed. Testing shows that the surface accuracy of the molded part is ±0.5mm, the surface roughness Ra≤1.6μm, the thickness distribution of the skin in the usable area is uniform, and the maximum thinning rate is controlled within 12%.

[0035] Step 3: Isothermal forging of the main beam cap and web. The channel-shaped cross-sections of the main beam cap and web were prepared using an isothermal compression molding process. The billet was preheated to 400℃ and held for 15 minutes. The molding temperature was 430℃, the unit pressure was 30MPa, the molding speed was 2mm / s, and the holding time was 120s. After molding, the flange width of the main beam cap was 60mm, the web height was 40mm, and the wall thickness was 2.5mm. The mold and the billet were kept at the same temperature throughout the molding process.

[0036] Tests showed that the isothermal forgings had a uniform microstructure, no cracks, folds or other defects, and a room temperature tensile strength (tested according to GB / T228.1-2021 standard) of 340 MPa and an elongation after fracture of 12%.

[0037] Step 4: Surface Treatment Stainless steel wire brushes are used to remove oxide scale and impurities from the surface of the molded parts; then, phosphate chemical conversion film treatment is performed to form a protective conversion film with a thickness of 2μm on the surface; finally, epoxy zinc-rich primer (thickness 35μm), epoxy intermediate paint (thickness 45μm) and polyurethane topcoat (thickness 45μm) are sprayed in sequence.

[0038] Step 5: Assembly The blades are assembled using a segmented bolt connection method. Flange structures are installed at the segment joints. The flange width is 80mm and the flange thickness is 2.5 times the skin thickness. High-strength bolts (M12, 12 bolts) are evenly arranged along the flange circumference. The number of bolts is calculated and determined according to the blade load according to the IEC61400-1 standard.

[0039] Example 2 (20m-class medium-sized magnesium alloy wind turbine blade) This embodiment takes the manufacturing of a 20m-class medium-sized magnesium alloy wind turbine blade as an example, and is applicable to MW-class wind turbine generator sets. The specific steps are as follows.

[0040] Step 1: Grain Refinement Pretreatment AZ31B magnesium alloy sheet was selected, with the following chemical composition by mass percentage: Al 3.2%, Zn 1.1%, Mn 0.6%, Si 0.04%, Cu 0.02%, Ni 0.003%, Fe 0.003%, and the balance being Mg. The sheet was heated to 400℃ and held for 4 hours, followed by four passes of warm rolling with reductions of 22%, 20%, 18%, and 15% per pass at a rolling temperature of 320℃. After this treatment, a superplastic billet with an average grain size of approximately 5 μm was obtained.

[0041] Step 2: Superplastic molding to create the skin Magnesium alloy sheet blanks are cut with a thickness of 4.5mm at the root area, 2.8mm in the middle area, and 1.8mm at the tip area, with a 300mm long gradient transition zone between each area.

[0042] The cut blank is placed into the thermoforming press mold, which is set at 460℃. A three-step pneumatic loading process is employed. Low-pressure rapid bonding stage: operating air pressure 0.22MPa, operating time 90s, operating temperature 460℃; Medium-pressure uniform extension stage: operating pressure 0.6 MPa, operating time 10 min, operating temperature 460℃, strain rate 2×10⁻⁶ -3 s -1 ; High-pressure precision molding stage: operating air pressure 1.1MPa, operating time 12min, operating temperature 460℃.

[0043] After molding, the mold temperature is reduced to below 200℃ at a rate of 8℃ / min while maintaining air pressure. Then, the pressure is released, the mold is opened, and the molded part is removed. Testing shows that the surface accuracy of the molded part is ±0.8mm, the surface roughness Ra≤1.6μm, the thickness distribution of the skin in the usable area is uniform, and the maximum thinning rate is controlled within 15%.

[0044] Step 3: Isothermal forging of the main beam cap and web. The channel-shaped cross-section of the main beam cap and web was prepared using an isothermal compression molding process. The billet was preheated to 420℃ and held for 20 minutes. The molding temperature was 450℃, the unit pressure was 50MPa, the molding speed was 5mm / s, and the holding time was 180s. After molding, the flange width of the main beam cap was 120mm, the web height was 80mm, and the wall thickness was 4.0mm.

[0045] Tests showed that the isothermal forgings had a uniform microstructure, no cracks, folds or other defects, a room temperature tensile strength of 350 MPa and an elongation at break of 11%.

[0046] Step 4: Surface Treatment The oxide scale and impurities on the surface of the molded parts are removed by sandblasting; then a zirconium salt chromium-free chemical conversion film treatment is performed (to replace chromate treatment and meet environmental protection requirements), forming a protective conversion film with a thickness of 3μm on the surface; finally, epoxy zinc-rich primer (thickness 40μm), epoxy intermediate paint (thickness 50μm) and fluorocarbon topcoat (thickness 50μm) are sprayed in sequence.

[0047] Step 5: Assembly The blades are assembled using a segmented bolt connection method. Flange structures are installed at the segment joints. The flange width is 120mm and the flange thickness is 3 times the thickness of the skin. High-strength bolts (M20, 24 bolts) are evenly arranged along the circumference of the flange. The number of bolts is calculated and determined according to the blade load according to the IEC61400-1 standard.

[0048] Comparative experiments and data analysis I. Comparative Experiment of Three-Step and One-Step Air Pressure Loading To verify the effectiveness of the three-step pneumatic loading process of this invention in controlling the uniformity of skin thickness, a comparative experiment was conducted on the skin forming of an 8m-class blade under the same material (AZ31B, average grain size 6μm) and the same temperature (430℃), using both one-step pneumatic loading (constant 0.6MPa) and the three-step pneumatic loading process of this invention (0.18MPa / 45s→0.5MPa / 8min→0.9MPa / 8min). The results are as follows:

[0049] Comparative experiments show that during one-step air pressure loading, the material deforms too rapidly in the initial stage, with a strain rate exceeding 5 × 10⁻⁶.-2 s -1 Exceeding the optimal strain rate range for superplastic deformation leads to localized excessive thinning and fracture. This invention addresses this by precisely controlling the gas pressure and deformation rate in stages, maintaining the strain rate at 1×10⁻⁶ at each stage. -3 ~5×10 -3 s -1 Within the specified range, it effectively suppressed uneven thickness and localized cracking.

[0050] II. The Influence of Different Grain Sizes on Superplastic Forming Effects To verify the effect of grain refinement pretreatment, AZ31B magnesium alloy sheets with average grain sizes of 6μm (pretreated according to this invention), 15μm (heated but not rolled), and 30μm (as-cast) were used to conduct a comparative experiment on superplastic gas expansion forming under the same process conditions. The results are as follows:

[0051] Comparative experiments show that grain size is a key factor in achieving superplasticity in magnesium alloys. When the grain size is ≤10μm, the material exhibits excellent superplasticity (elongation >500%) at 430℃; when the grain size is >10μm, the superplasticity decreases significantly, with the elongation of 15μm grains being only 29% of that of 6μm grains, and 30μm cast grains even failing to complete gas-expansion forming. This invention, through a grain refinement pretreatment of heating and holding followed by multi-pass warm rolling, controls the grain size to 3–8μm, providing an ideal material basis for subsequent superplastic forming.

[0052] III. Influence of Different Isothermal Forging Temperatures on the Mechanical Properties of the Main Beam Cap To verify the reasonable range of isothermal forging temperature, main beam cap samples were forged at different temperatures (380℃, 400℃, 430℃, 460℃, and 480℃) while keeping other process parameters constant (unit pressure 30MPa, forging speed 2mm / s, holding time 120s). The test results are as follows:

[0053] Comparative experiments show that the best balance between formability and mechanical properties can be achieved when the forging temperature is 400–460℃. Below 400℃, insufficient material fluidity leads to incomplete filling; above 460℃, the grains coarsen significantly (>15μm), and according to the Hall-Petch relationship, the room temperature tensile strength decreases significantly (from 340MPa to 295MPa).

[0054] IV. Weight Comparison 8m-class blade: The total weight of the 8m-class magnesium alloy wind turbine blade manufactured in Example 1 is approximately 65 kg. A conventional glass fiber composite blade of the same specification (manufactured using vacuum injection molding) weighs approximately 110 kg. The magnesium alloy blade represents a weight reduction of approximately 40.9% compared to the conventional glass fiber composite blade.

[0055] 20m-class blade: The total weight of the 20m-class magnesium alloy wind turbine blade manufactured in Example 2 is approximately 420 kg. The weight of a conventional fiberglass composite blade of the same specification is approximately 720 kg. The magnesium alloy blade represents a weight reduction of approximately 41.7% compared to the conventional fiberglass composite blade.

[0056] Magnesium alloy has a density of approximately 1.8 g / cm³. 3 The density of glass fiber composites is 1.5–2.0 g / cm³. 3 Although both have similar densities, magnesium alloys have higher specific strength (approximately 130–150 kN·m / kg, while glass fiber composites are approximately 60–90 kN·m / kg), allowing for thinner cross-section designs and better weight reduction while meeting the same structural strength requirements.

[0057] V. Comparison of Manufacturing Efficiency For 8m-class blades: In this example, the superplastic gas expansion molding time (including three stages) for the skin is controlled at approximately 16.75 minutes (45s + 8min + 8min), plus a slow cooling time of approximately 30 minutes, resulting in a total molding time of less than 50 minutes for a single skin. Traditional vacuum infusion processes for manufacturing glass fiber composite blades of the same specifications typically require 24–48 hours for epoxy resin infusion and curing in the mold. The magnesium alloy superplastic molding process increases the blade skin molding efficiency by tens of times (approximately 29 times for 24 hours and approximately 58 times for 48 hours).

[0058] For 20m-class blades: In this example, the superplastic gas-expansion molding time for the skin in Example 2 is approximately 22.75 minutes (90s + 10min + 12min), with a slow cooling time of approximately 40 minutes, resulting in a total molding time of less than 65 minutes for a single skin. Traditional vacuum infusion processes for manufacturing 20m-class glass fiber composite blades typically have a molding cycle exceeding 48 hours due to the longer resin infusion path and curing time. The efficiency advantage of magnesium alloy superplastic molding is even more pronounced for larger blades.

[0059] VI. Comparison of Fatigue Performance To verify the long-term service reliability of magnesium alloy blades, fatigue tests were conducted on an 8m-class magnesium alloy blade (Example 1) and a glass fiber composite blade of the same specification. The test method was as follows: a sinusoidal cyclic load (load amplitude 30% of the design limit load, stress ratio R=0.1, frequency 1Hz) was applied in the blade flapping direction. The test results are as follows:

[0060] Fatigue test results show that the magnesium alloy blades can withstand 2×10 7 No failure was observed after several cycles, demonstrating fatigue performance superior to traditional composite blades. Magnesium alloys are isotropic materials, eliminating the delamination issues common in composite materials, and thus exhibit better damage tolerance and detectability.

[0061] VII. Comparison of Recyclability The biggest drawback of traditional glass fiber / carbon fiber-epoxy resin composite wind turbine blades is their non-recyclability. The epoxy resin matrix is ​​a thermosetting material, difficult to decompose and regenerate after disposal, leaving the blades to be landfilled or incinerated after retirement, causing a severe environmental burden. This invention uses a magnesium alloy to replace the traditional composite material, which has the advantage of being 100% recyclable.

[0062] As can be seen from the above embodiments and comparative data, the present invention uses magnesium alloy to replace traditional glass fiber / carbon fiber-epoxy resin composite materials in the manufacture of wind turbine blades, achieving improvements in lightweighting (weight reduction of more than 40%), manufacturing efficiency (increased by tens of times), environmental friendliness (100% recyclable), and fatigue performance (>2×10⁻⁶). 7 Significant progress has been made in all four aspects (secondary, primary, and secondary), which is particularly suitable for the urgent needs of wind power equipment to develop towards larger size, lighter weight, and greener characteristics.

[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for manufacturing a magnesium alloy wind turbine blade, characterized in that: Includes the following steps: Step 1: Perform grain refinement pretreatment on magnesium alloy sheet to obtain superplastic billet with an average grain size ≤10μm; Step 2: The windward and leeward skins of the magnesium alloy wind turbine blades are manufactured using a superplastic forming process. The superplastic forming is carried out in a dedicated thermoforming press, and the forming process includes a low-pressure rapid bonding stage, a medium-pressure uniform stretching stage, and a high-pressure precision molding stage. Step 3: Manufacture the main beam cap and web using isothermal forging technology; Step 4: The formed magnesium alloy wind turbine blades need to undergo surface treatment; Step 5: Assemble the windward skin, leeward skin, main beam cap, and web into a magnesium alloy wind turbine blade.

2. The method for manufacturing a magnesium alloy wind turbine blade according to claim 1, characterized in that: The magnesium alloy sheet comprises the following substances in mass percentage: Al 2.5-3.5%, Zn 0.7-1.3%, Mn 0.2-1.0%, Si ≤0.10%, Cu ≤0.05%, Ni ≤0.005%, Fe ≤0.005%, with the remainder being Mg.

3. The method for manufacturing a magnesium alloy wind turbine blade according to claim 1, characterized in that: The grain refinement pretreatment is as follows: heating the magnesium alloy sheet to 350-420℃ and holding it for 2-4 hours, followed by 2-4 passes of warm rolling, with a reduction of 15%-25% per pass and a rolling temperature of 250-350℃.

4. The method for manufacturing a magnesium alloy wind turbine blade according to claim 1, characterized in that: The manufacturing process of the windward and leeward skins of the magnesium alloy wind turbine blades is as follows: Step 1: Cutting magnesium alloy sheet blanks; Step 2: Segmented molding of the skin: Place the cut magnesium alloy sheet blanks into the mold; Step 2-1: Low-pressure rapid bonding; Step 2-2: Uniform extension under medium pressure; Steps 2-3: High-pressure precision molding; Step 3: Open the mold and remove the parts.

5. The method for manufacturing a magnesium alloy wind turbine blade according to claim 4, characterized in that: The cutting thickness of the magnesium alloy sheet blank used for the root region (connection section with the wheel hub) is 3.0-5.0 mm; the cutting thickness of the magnesium alloy sheet blank used for the middle region is 2.0-3.0 mm; the cutting thickness of the magnesium alloy sheet blank used for the blade tip region is 1.5-2.0 mm; a gradual transition is adopted between each region, and the length of the transition zone is not less than 200 mm.

6. The method for manufacturing a magnesium alloy wind turbine blade according to claim 4, characterized in that: The operating air pressure for the low-pressure rapid bonding of the segmented skin manufacturing process is 0.15–0.25 MPa, the operating time is 30–120 s, and the operating temperature is 400–500 °C. The operating pressure for the segmented manufacturing of the aforementioned skin, characterized by medium-pressure uniform expansion, is 0.4–0.7 MPa, the operating time is 8–10 min, and the operating temperature is 400–500 °C, at a rate of 1 × 10⁻⁶. -3 ~5×10 -3 s -1 The strain rate allows the material to fully extend and fill the mold cavity; The operating air pressure for the high-pressure precision molding of the skin segment manufacturing process is 0.8–1.2 MPa, the operating time is 5–15 min, and the operating temperature is 400–500 °C.

7. The method for manufacturing a magnesium alloy wind turbine blade according to claim 4, characterized in that: After the skin segment molding process is completed, the mold temperature is reduced to below 200°C at a rate of 5-15°C / min while maintaining air pressure. Then, the pressure is released, the mold is opened, and the molded part is removed.

8. The method for manufacturing a magnesium alloy wind turbine blade according to claim 1, characterized in that: The operation of manufacturing the main beam cap and web plate using the isothermal die forging technology is as follows: the grooved cross-section of the main beam cap and web plate is prepared by isothermal die forging, the die forging temperature is 400-460℃, the unit pressure is 10-80MPa, the die forging speed is 0.5-10mm / s, the holding time is 30-300s, the billet preheating temperature is 350-450℃, the preheating time is 10-30min, the flange width is 50-150mm, the web plate height is 30-100mm, and the wall thickness is 2.5-5.0mm.

9. The method for manufacturing a magnesium alloy wind turbine blade according to claim 1, characterized in that: The surface treatment of the magnesium alloy wind turbine blades after forming is as follows: removing surface oxide scale and impurities using a stainless steel wire brush or sandblasting; then performing chemical conversion film treatment: using phosphate or chromate treatment to form a protective conversion film on the surface, the thickness of which is 1-5 μm; finally, applying an organic coating, which includes an epoxy zinc-rich primer, an epoxy intermediate coat, and a polyurethane or fluorocarbon topcoat, the thickness of which is 30-50 μm, the thickness of which is 40-60 μm, and the thickness of which is 40-60 μm.

10. The method for manufacturing a magnesium alloy wind turbine blade according to claim 1, characterized in that: The magnesium alloy wind turbine blades are assembled using segmented bolt connections, with flange structures at the segment joints. The flange width is 50–150 mm, and the flange thickness is 2–3 times the thickness of the skin. High-strength bolts are evenly arranged along the circumference of the flange, and the number of bolts is determined based on load calculations.